Interfaith Marriage: Between Pro and Contra In Islamic Jurist's Thought - Suwarjin Suwarjin (Jurnal Madania)
Interfaith marriage is remained a topic of discussion, especially since the appearance of an application to the Constitutional Court (MK/ Mahkamah Konstitusi) for a judicial review of the marriage law. The decision of the Constitutional Court did not satisfy various parties because the application was rejected because the validity of interfaith marriages is the territory of each religion to decide on it. From here, the pros and cons of interfaith marriage reappear. This article aims to examine the pros and cons of the views of Islamic jurists' thoughts on the legitimacy of interfaith marriages, both from classical scholars and from various groups and mass organizations in Indonesia. This article aims to examine the views of the pros and cons of the validity of interfaith marriages, especially in Islam, both from classical scholars and from various groups and mass organizations in Indonesia. The approach used is classical ushul fiqh to analyze and compare the various views and then synthesize and select the most appropriate views. From this study, it was concluded that the view of the majority of scholars who only allow interfaith marriages between Muslims and ahl al-kitab is a view that is more in line with the theory of ushul fiqh. Besides that, marriage between ahl al-kitab men and Muslim women can also be legalized with the qiyas approach, whose illat is wisdom.